Questions a patient with moderate to severe atopic dermatitis would like to be asked: Data from a qualitative study conducted by anthropologists - Judith Nicogossian; Stéphane Héas; Claire Thénié; Margaux Noel; Laurent Misery; Sebastien Barbarot; Fabienne Martin Juchat (Wiley, 2024)
Abstract Background A considerable number of patients with moderate to severe atopic dermatitis (AD) are undertreated and have inadequate control of their symptoms leading to a hight patient dissatisfaction during their care. The VECUDA study composed of VECU and DA for french word lived and atopic dermatitis was conducted by anthropologists in cooperation with dermatologists, aimed to better understand the complexity of the care pathway and the physician‐patient relationship by questioning patients with moderate to severe AD. Objectives The aim was to identify patient's needs and to propose concrete ways of improving the doctor‐patient relationship by focusing on the narrative of their affects. Co‐designed easy‐to‐use tools were proposed by these patients. Methods The exploratory qualitative study involved 24 patients with moderate‐to‐severe AD. The study was conducted in two stages: a codesign phase with four patients, and a deepening phase with all patients (24), supported by a multidisciplinary scientific committee. During group interviews, conducted using creativity tools, patients' stories related to their experiences of the disease and its management were collected. Results By studying the patients' affect stories, researchers were able to identify the needs of patients who might be 1. emotional (better consideration of their experiences); 2. informational (more information about their disease and treatments); 3. participatory (being involved in their care: therapeutic alliance). Mechanisms of therapeutic dissatisfaction and satisfaction were mapped into vicious and virtuous circles. Patients also offered concrete and easy‐to‐use tools. We are presenting here the grid of questions these patients would like to be asked during their doctor's appointment: the Doctor‐Facing Questions Grid that these patients would like to be asked during a consultation. Conclusions By facilitating the identification of patients' needs/expectations, these tools would help guide the clinician's discussion and management in a few questions. The VECUDA study confirms the value of considering patients' perspective as a lever for improving the doctor‐patient relationship.